KRISIS INFLASI GLOBAL DAN SOLUSI STABILITAS HARGA DALAM EKONOMI ISLAM - Dini Sasmita Sari; Ichsan Iqbal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The wave of global inflation that has engulfed almost the entire world economy following the COVID-19 pandemic and the escalation of the Russia-Ukraine geopolitical conflict has exposed deep structural vulnerabilities in the conventional economic system based on usury, speculation, and uncontrolled credit expansion. This study aims to comprehensively analyze the phenomenon of the global inflation crisis and elaborate on price stability solutions offered by Islamic economic principles. The method used is a qualitative approach with a literature study design (library research), utilizing content analysis techniques on relevant primary and secondary sources, including official reports of international institutions, articles from accredited national journals, reputable international journals, and academic books on Islamic economics. The results show that the global inflation crisis was triggered simultaneously by supply chain disruptions, spikes in energy prices, a food crisis due to geopolitical conflicts, and expansionary monetary policies that resulted in a liquidity surplus without a basis in real productivity. Islamic economics diagnoses inflation not only as a monetary phenomenon, but also as a manifestation of systemic injustice stemming from the practices of usury, ikhtikar (hoarding), and gharar (excessive speculation). The solutions offered include profit-sharing-based monetary reform, enforcing the prohibition on ikhtikar through the institution of hisbah, optimizing zakat and waqf as automatic stabilizers of wealth distribution, and implementing sharia fiscal policies oriented towards meeting the dharuriyyat needs of society. The maqasid sharia framework has proven relevant as a normative foundation for designing price stability policies that are not only economically effective but also socially just and ethically dignified in the context of a modern economy.